Bone marrow biopsy in the initial staging of Ewing sarcoma: Experience from a single institution. Issue 6 (5th February 2019) - Cesari, Marilena; Righi, Alberto; Colangeli, Marco; Gambarotti, Marco; Spinnato, Paolo; Ferraro, Andrea; Longhi, Alessandra; Abate, Massimo Eraldo; Palmerini, Emanuela; Paioli, Anna; Ferrari, Cristina; Donati, Davide Maria; et al.
Abstract: Background: Ewing sarcoma (ES) is the second most common bone tumor in adolescents and children. Staging workup for ES includes imaging and bone marrow biopsy (BMB). The effective role of BMB is now under discussion. Procedure: A monoinstitutional retrospective analysis reviewed clinical charts, imaging, and histology of patients with diagnosis of ES treated at the Rizzoli Institute between 1998 and 2017. Results: The cohort included 504 cases of ES of bone; 137 (27%) had metastases at diagnosis, while the remaining 367 had localized disease. Twelve patients had a positive BMB (2.4%). Eleven had distant metastases detected at initial workup staging with imaging assessment: six patients presented with bone metastases, five with both bone and lung metastases. Only one patient with ES of the foot (second metatarsus) was found to have bone marrow involvement with negative imaging evaluation (0.3%). Conclusions: On the basis of our data, we suggest reconsidering the effective role of BMB in initial staging workup for patients with ES with no signs of metastases by modern imaging techniques. In metastatic disease, the assessment of the bone marrow status may remain useful to identify a group of patients at very high risk who could benefit from different treatment strategies.